A study of partnering relationship between shipper and carrier in Singapore : issues, ranking and satisfaction - Koh, Yong Jie. (2010)
The objective of this research project is to identify, examine and compare standings of key service attributes of partnerships between carriers and shippers in addition to determining the overall satisfaction level of organisations towards partnering relationships. Data collection, conducted via surveys and interviews, targeted at relevant Singapore-registered companies. It was observed that shippers and carriers were satisfied with their current partners. A total of sixteen service attributes were also found to be valid and substantially vital for partnerships. Service reliability and consistency was found to be more important than Freight rates. Other key service attributes ascertained were Willingness to meet service expectation, Availability of cargo space and Accurate billing and documentation. However, there were noteworthy disparities between the perceptions of shippers and carriers on the importance of each service attribute. Hypothesis testing determined eleven service attributes experienced significant differences between shippers and carriers’ responses. In addition, service attributes highlighted by shippers for improvement did not match those earmarked by carriers. Fortunately, for the wet bulk segment, shippers and carriers concur largely on the top five attributes to develop further despite differences in mean-score ranking of the service attributes. This study underscores an evident lack of appreciation for shippers’ concerns by carriers as well as the deficiency in communications and coordination between the two major stakeholders of partnerships.